Equal Access to American Higher Education: Reality or Fiction? - Ruiz Santiago, Silvia María (2022)
American democratic values and ideals affirm that all people have the same chance of success regardless of race, ethnicity, or gender. The equal opportunities that all students must have do not apply to all educational institutions in this country. Leadership theory, instructional as well as evaluative practices have had and still have a great impact on this inequality. In this regard, educational leaders need to put a brake on the policy they are enforcing to balance resources and provide everything needed for an education tailored to all social classes. Higher education should be the means of educating a multicultural society where neither color, race, origin, nor the gender of people comes first. Educational equity must be present in each of the institutions to offer the educated equal opportunities to seek universal social justice.